2022
DOI: 10.1021/acs.jctc.2c00313
|View full text |Cite
|
Sign up to set email alerts
|

How Good Is the Density-Corrected SCAN Functional for Neutral and Ionic Aqueous Systems, and What Is So Right about the Hartree–Fock Density?

Abstract: Density functional theory (DFT) is the most widely used electronic structure method, due to its simplicity and cost effectiveness. The accuracy of a DFT calculation depends not only on the choice of the density functional approximation (DFA) adopted but also on the electron density produced by the DFA. SCAN is a modern functional that satisfies all known constraints for meta-GGA functionals. The density-driven errors, defined as energy errors arising from errors of the self-consistent DFA electron density, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 113 publications
1
56
0
Order By: Relevance
“…In contrast, DRSLL-opt88, which was optimized for van der Waals and hydrogen-bonding interactions, and SCAN, which is a nonempirical functional that satisfies all 17 constraints known for meta-GGA functionals, predict a more structured first hydration shell that is shifted toward shorter distances, in better agreement with the (2B+3B+NB)-MB-nrg results. In this context it should be noted that recent studies demonstrated that several density functionals suffer from both functional- and density-driven errors, which significantly affect their performance when applied to aqueous systems. In particular, large density-driven errors were found in SCAN calculations for pure water systems as well as for ions in water, ,, which suggests that the apparent agreement between the RDFs calculated from MD simulations with the SCAN functional and the (2B+3B+NB)-MB-nrg PEF may result from error cancellation in the SCAN representation of water–water and ion–water interactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, DRSLL-opt88, which was optimized for van der Waals and hydrogen-bonding interactions, and SCAN, which is a nonempirical functional that satisfies all 17 constraints known for meta-GGA functionals, predict a more structured first hydration shell that is shifted toward shorter distances, in better agreement with the (2B+3B+NB)-MB-nrg results. In this context it should be noted that recent studies demonstrated that several density functionals suffer from both functional- and density-driven errors, which significantly affect their performance when applied to aqueous systems. In particular, large density-driven errors were found in SCAN calculations for pure water systems as well as for ions in water, ,, which suggests that the apparent agreement between the RDFs calculated from MD simulations with the SCAN functional and the (2B+3B+NB)-MB-nrg PEF may result from error cancellation in the SCAN representation of water–water and ion–water interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In this context it should be noted that recent studies demonstrated that several density functionals suffer from both functional-and density-driven errors, which significantly affect their performance when applied to aqueous systems. 47−52 In particular, large density-driven errors were found in SCAN calculations for pure water systems as well as for ions in water, 48,51,52 which suggests that the apparent agreement between the RDFs calculated from MD simulations with the SCAN functional and the (2B+3B+NB)-MB-nrg PEF may result from error cancellation in the SCAN representation of water−water and ion−water interactions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…46 Recent analyses have shown that the different performance of a given density functional in describing pure water and ions in water can be rationalized by considering the interplay between functional-and density-driven errors. [47][48][49][50][51][52] Despite much progress in characterizing the hydration properties of ions in water, a transferable molecular model capable of correctly predicting structural, thermodynamic, and dynamical properties of hydrated ions from small aqueous clusters in the gas phase to aqueous solutions and interfaces is still missing. In the past years, we introduced the many-body energy (MB-nrg) theoretical/computational framework for data-driven manybody potential energy functions (PEFs).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, it should be noted that recent studies demonstrated that several density functionals suffer from both functional-and density-driven errors which significantly affect their performance when applied to aqueous systems. [47][48][49][50][51][52] In particular, large density-driven errors were found in SCAN calculations for pure water systems as well as for ions in water, 48,51,52 which suggests that the apparent agreement between the RDFs calculated from MD simulations with the SCAN functional and the (2B+3B+NB)-MB-nrg PEF may result from error cancellation in the SCAN representation of water-water and ion-water interactions.…”
mentioning
confidence: 99%
“…The first and perhaps most significant problem is that the DFT functionals used to generate the training data can have significant inaccuracies associated with them. [90][91][92][93] One potential solution to this problem is to add correction potentials adjusted to minimise this error using either higher level calculations on small clusters 39,42,94 or experimental information. Using machine learning to determine the corrections is also a possibility.…”
Section: Ab Initio Accuracymentioning
confidence: 99%